Strategi Kepala Sekolah Meningkatkan Karakter Siswa Berbasis Kearifan Lokal “Silat Pelintau ” Pada Sekolah Dasar di Kabupaten Aceh Tamiang - Heri Kurnila; Najmuddin Najmuddin; Sari Rizki (JAMP : Jurnal Administrasi dan Manajemen Pendidikan, 2026)
Abstract: This study aims to analyze the principal’s strategy in integrating the local wisdom values of Silat Pelintau into character education programs in elementary schools in Aceh Tamiang Regency. The focus of the study is directed at how principals plan, organize, implement, and evaluate the Silat Pelintau program as a medium for shaping students’ character, while also identifying obstacles and formulating recommendations for program development. This study employed a qualitative approach with a case study design. The research informants included principals, classroom teachers, physical education teachers, Silat Pelintau trainers, studio leaders, and community figures who understand the practice of Pelintau culture. Data were collected through in-depth interviews, field observations, and document analysis, and were then analyzed through data reduction, data display, conclusion drawing, and thematic coding assisted by NVivo. The findings indicate that the principal’s strategy was implemented through four main stages: program planning within school and extracurricular activities, organizing the roles of teachers and trainers, implementing Silat Pelintau training adapted to the characteristics of elementary school students, and evaluating character development through observation and discussions with teachers and trainers. The integration of Silat Pelintau was found to contribute to strengthening the values of discipline, responsibility, politeness, courage, perseverance, cooperation, emotional control, and love for the local culture of Aceh Tamiang. The obstacles identified include limited facilities, time allocation, fluctuating student motivation, the absence of official curriculum guidelines, and the suboptimal documentation of the program in learning documents. Strategic recommendations emphasize the need to strengthen school policies, establish a memorandum of understanding with local studios, provide teacher training, enhance multi-stakeholder collaboration, and develop sustainable programs. Theoretically, this study enriches the discourse on character education based on local wisdom; practically, its findings may serve as a reference for principals, teachers, studios, and local governments. The findings also highlight the importance of principal leadership in ensuring the sustainability of local culture-based character education programs. This study affirms that Silat Pelintau has the potential to serve as a contextual, applicable, and relevant model of character education for elementary school students. Keywords: Principal strategy; Character education; Local wisdom; Silat Pelintau ; Elementary school. Abstrak: Penelitian ini bertujuan untuk menganalisis strategi kepala sekolah dalam mengintegrasikan nilai-nilai kearifan lokal Silat Pelintau ke dalam program pendidikan karakter pada sekolah dasar di Kabupaten Aceh Tamiang. Fokus penelitian diarahkan pada bagaimana kepala sekolah merencanakan, mengorganisasikan, melaksanakan, dan mengevaluasi program Silat Pelintau sebagai media pembentukan karakter siswa, sekaligus mengidentifikasi kendala dan merumuskan rekomendasi pengembangan program. Penelitian ini menggunakan pendekatan kualitatif dengan desain studi kasus. Informan penelitian meliputi kepala sekolah, guru kelas, guru olahraga, pelatih Silat Pelintau, pimpinan sanggar, dan tokoh masyarakat yang memahami praktik budaya Pelintau. Data dikumpulkan melalui wawancara mendalam, observasi lapangan, dan telaah dokumentasi, kemudian dianalisis menggunakan teknik reduksi data, penyajian data, penarikan kesimpulan, serta coding tematik berbantuan NVivo. Hasil penelitian menunjukkan bahwa strategi kepala sekolah dilakukan melalui empat tahapan utama, yaitu perencanaan program dalam kegiatan sekolah dan ekstrakurikuler, pengorganisasian peran guru dan pelatih, pelaksanaan latihan Silat Pelintau yang disesuaikan dengan karakteristik siswa sekolah dasar, serta evaluasi perkembangan karakter melalui observasi dan diskusi bersama guru maupun pelatih. Integrasi Silat Pelintau terbukti berkontribusi terhadap penguatan nilai disiplin, tanggung jawab, sopan santun, keberanian, ketekunan, kerja sama, pengendalian emosi, dan kecintaan terhadap budaya lokal Aceh Tamiang. Kendala yang ditemukan meliputi keterbatasan fasilitas, alokasi waktu, motivasi siswa yang fluktuatif, belum adanya panduan kurikulum resmi, serta belum optimalnya dokumentasi program dalam perangkat pembelajaran. Rekomendasi strategis menekankan perlunya penguatan kebijakan sekolah, penyusunan Kerjasama dengan sanggar, pelatihan guru, kolaborasi multipihak, dan pengembangan program berkelanjutan. Secara teoretis, penelitian ini memperkaya kajian pendidikan karakter berbasis kearifan lokal; secara praktis, hasilnya dapat menjadi acuan bagi kepala sekolah, guru, sanggar, dan pemerintah daerah. Temuan ini juga menunjukkan pentingnya kepemimpinan kepala sekolah dalam menjaga kesinambungan program karakter berbasis budaya lokal. Penelitian ini menegaskan bahwa Silat Pelintau memiliki potensi sebagai model pendidikan karakter yang kontekstual, aplikatif, dan relevan bagi siswa sekolah dasar. Kata kunci: Strategi kepala sekolah; Pendidikan karakter; Kearifan lokal; Silat Pelintau ; Sekolah dasar